TANTANGAN TURBULENSI EKONOMI GLOBAL TERHADAP EKONOMI POLITIK INTERNASIONAL INDONESIA - Rafli Zulfikar; Akhmad Jayadi (EP FEB UNS, 2017)
This paper analyzes Indonesia's political economy amid the global economic turbulence. The global economy experiencing Volatility, Uncertainly, Complexity, Ambiguity (VUCA) makes the correction of the world economic performance. The factors are not only based on the international economy but also because of changes in international politics, international security and global geopolitics. The absence of global economic locomotive makes the global economic recovery agenda is slow and long. This paper discusses the mitigation of Indonesia in the face of global economic turbulence and alternatives that can be selected Indonesia.Keyword: global economy, economic slowdown, Indonesia